2015
DOI: 10.1161/circulationaha.114.012461
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Surgical Indications, Operative Risk, and Clinical Outcome in Infective Endocarditis

Abstract: T he decision to perform surgery in infective endocarditis (IE) remains a challenge because of the potential for acute and life-threatening complications of this disease, uncertain response to antibiotic therapy, and comorbid host conditions. Cardiac surgery is used in combination with antibiotics for the treatment of IE in ≈50% of affected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
67
3
14

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 232 publications
(108 citation statements)
references
References 40 publications
8
67
3
14
Order By: Relevance
“…Our recent study of surgical indications and treatment in the ICE‐PLUS cohort found that approximately one‐quarter of left‐sided IE cases with indications for surgery did not undergo surgery due to operative risk factors, such as sepsis, but that surgery was associated with a survival benefit after adjustment for operative risk 12. The present study highlights the risk of death related to host and IE characteristics even beyond the period of surgical intervention.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Our recent study of surgical indications and treatment in the ICE‐PLUS cohort found that approximately one‐quarter of left‐sided IE cases with indications for surgery did not undergo surgery due to operative risk factors, such as sepsis, but that surgery was associated with a survival benefit after adjustment for operative risk 12. The present study highlights the risk of death related to host and IE characteristics even beyond the period of surgical intervention.…”
Section: Discussionmentioning
confidence: 61%
“…Regional differences in IE characteristics and treatment may exist within the cohort, but sensitivity analysis by geographic region did not substantially change the hazard ratios for mortality in the derivation model. The use of surgery was not prespecified by a study protocol, but we have previously found that surgery was performed for guideline‐directed indications6, 7 in the ICE‐PLUS cohort 12. Although treatment selection bias for surgery may influence the results of the present study, surgical intervention was evaluated as a time‐dependent variable with inverse probability adjustment for surgery in both models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39,47 In HICs, approximately half of IE patients in reported prospective series' undergo surgical intervention, 1,2,62 with up to 75% of patients with indications for surgery receiving it. 62 In our reviewed studies, although UMIC studies reported surgical intervention rates close to HICs, two lower middle-income country studies reported low rates of 0% and 15%. 19,20 We however found no information on the rates of surgical intervention among patients with indications for surgery, however, given the high rate of complications among IE patients in our reviewed studies, we can conclude that this rate was low.…”
Section: Dismal Access To Surgerymentioning
confidence: 81%
“…Esto, con base en el reconocimiento de las características de alto riesgo que impiden que el tratamiento antibiótico per se resuelva por completo la infección; entre tales características están: la insuficiencia cardíaca progresiva, la infección no controlada y fenómenos embólicos a repetición, a pesar del tratamiento antibiótico apropiado. El tratamiento quirúrgico es de alta morbilidad, por lo que se debe seleccionar cuidadosamente a los pacientes, con el fin de obtener los mayores beneficios de la intervención, y aunque el tiempo depende de cada situación específica, se sugiere que sea en forma temprana, idealmente en las primeras 48 horas (32). Las indicaciones más frecuentes para plantear el tratamiento quirúrgico fueron: desarrollo de falla cardía-ca, fenómenos embólicos recurrentes a pesar de un tratamiento médico óptimo, bacteriemia persistente, formación de abscesos perivalvulares, el tamaño de la vegetación y el tipo de microorganismo (32,33).…”
Section: Tratamientounclassified